Determination of heavy metals and essential minerals in water, soil and edible plant samples from the vicinity of ankpa coal mine, kogi state - Zubairu, Nimatu; Mohammed, Yau; Babatunde, O. Abiodun; salawu, john (International Journal of Advanced Chemistry, 2022)
This research work determined the physicochemical properties (pH, temperature, electrical conductivity, total dissolved solids and total suspended solids) of water, heavy metals (Cr, Cd, Cu, Pb and Zn) and essential minerals ( P, Ca, K, Mg and Na) in water, plant and soil samples collected from the vicinity of Ankpa Coal mine, Kogi State. The heavy metals were analyzed using a Flame Atomic Absorption Spectrophotometer machine and the essential minerals analyzed using Microwave Plasma Atomic Emission Spectrophotometer machine. Results obtained for physical parameters of water are within the ranges; pH (4.51-6.91), temperature (19.8-26.5˚C), electrical conductivity (110-210 µs/cm), TDS (7.0-13 mg/l) and TSS (0-1.5 mg/l). The heavy metals concentration in water are as follows; Cd (ND), Pb (0.001-0.077 mg/l), Cr (0.028-3.459 mg/l), Cu (0.09-0.057 mg/l) and Zn (0.050-0.161 mg/l). In plants, Cd (ND), Pb (0.043-0.096 mg/kg), Cr (0.138-0.325 mg/kg), Cu (0.139-0.153 mg/kg) and Zn (0.150-0.510 mg/kg). In soils, Cd (ND), Pb (0.127-0.664 mg/kg), Cr (1.206-4.718 mg/kg), Cu (0.155-0.934 mg/kg) and Zn (0.00-0.400 mg/kg). Results obtained for essential minerals ranged as follows; In water, P (0.19-43.31 mg/l), Ca (5.75-158.63 mg/l), K (5.04-32.28 mg/l), Mg (1.98-11.34 mg/l) and Na (10.70-28.29 mg/l). In plants, P (15.12-23.90 mg/kg), Ca (30.13-144.44 mg/kg), K (64.10-119.06 mg/kg), Mg (10.38-25.69 mg/kg) and Na (0.94-3.55 mg/kg). In soil, P (180.01-1879.51 mg/kg), Ca (11.61-85.18 mg/kg), K (3.02-114.98 mg/kg), Mg (2.59-14.05 mg/kg) and Na (8.24-15.03 mg/kg). The results were compared with the maximum permissible limit (MPL) set by World Health Organization (WHO), Food and Agricultural Organization (FAO) and recommended dietary intake set by Food and Nutrition Board (FNB). The physicochemical parameters were all within WHO maximum permissible limit for drinking water. Lead and Cr exceeded the MPL set for drinking water, all heavy metals were within set limit for plants. Lead, Cu and Chromium exceeded the MPL set for soil. The essential minerals in all samples were compared to recommended dietary intake (RDI). Correlation analysis was done using Pearson’s correlation coefficient. In plants Zn correlated positively with Ca (0.9298), K (0.7860) and Mg (0.9967) and in soil samples Cu correlated positively with P (0.8212), K (0.8191) and Na (0.8658), Cr correlated positively with P (0.9911), K (0.9915) and Na (0.8363) and Lead correlated positively with P (0.9734), K (0.9905) and Na (0.7948). It can be inferred from this result that Ankpa coal mine has negatively impacted its vicinity.